Error Optimization in Electrical Power Quality Monitoring Data - Isdawimah Isdawimah (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2019)
In the application of electrical power quality control, the necessity for data processing becomes very important. The measurement data obtained is the latest data and measured in real time with good time resolution and with low error. The object of research is the quality of electric power, the research is about ways of measuring quality of electrical power to obtain accurate data in accordance with actual conditions. This method is capable of measuring data of electrical power quality that changes very quickly with a low error. This data is used as a basis for improving the quality of electric power accurately and accurately.